Trend Analysis of the Value Added Tax in Nepal - Sutihar, Deo Narayan (Economic Literature, 2018)
Value added tax (VAT) is the recent one of the sales tax family. This article tries to estimate the share of VAT in Gross Domestic Product (GDP), total tax revenue and indirect tax revenue. Besides, it also estimates the growth rate of VAT. This comprises 2.80 percent and 16.01 percent share of GDP in fiscal year 2000/01 and 2014/15 respectively. It also ranges from 30.69 percent to 37.63 percent share of tax revenue. Likewise, its share ranges from39.94 percent to 50.05 percent. The regression equation has been used to estimate annual growth rate of VAT. The estimate of the annual growth rate of VAT is found to be Rs.6.63billion. From this result, it is obvious that VAT has been increased by Rs. 6.63 billion annually during study period of the fifteen years. The coefficient of determination (R2) shows 87.76% of the total variation in VAT is explained by the variation in time variable. Similarly, the adjusted coefficient of determination (R2) exhibits that 86.82% of the total variance in VAT is explained by the variance in time variable. The calculated value of F-distribution is found to be 93.204, which is greater than critical value of F i.e. F0.05 (1,13)=4.67. It is significant at 5% level, which exhibits the best fitted regression line. From the statistical analysis, the value of autocorrelation is found to be 0.54 and its d-statistic is also found, which is significant at 5 percent level. Thus, the analysis justifies that there is a positive autocorrelation among error terms. To remove the autocorrelation, the transformation data have been used. But, the value of autocorrelation is not found corrected which needs by incorporating other important explanatory variables to further research. Economic Literature, Vol. XIII August 2016, page 1-8